HUBUNGAN ASUPAN ZAT GIZI DAN PENGUKURAN ANTROPOMETRI DENGAN KEBUGARAN JASMANI MAHASISWI PEMINATAN GIZI 2018 FKM UNDIP - Wijayanti, Deti; Rahfiludin, M. Zen; Suroto, Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Physical fitness is the ability to carry out daily activities without feeling exhausted efficiently and effectively. To get the optimum physical fitness, nutrition intake is needed Nutrition intake is needed to obtain the optimum performance and help growth. This study aims to determine the relation between nutrient intake and anthropometric measurements with physical fitness of nutritional students of Public Health Faculty Diponegoro University 2018. This research isquantitative study with cross sectional study design.The population is all 2018 Public Health Nutrition students aged 20-22 years at the Faculty of Public Health, Diponegoro University, Semarang. Sample is taken by the used of purposive sampling technique. Data were analyzed using Pearson Product Moment correlation test and Spearman rank. The results showed that the level of energy intake was classified as lacking (69.6%), carbohydrate intake classified as lacking (69.6%), protein intake classified as lacking (45.7%), and fat intake was also lacking (80.4%). Body fat percentage classified as Latent Obese (32.6%), as well as Physical fitness classified as very lacking (67.4%). The results showed no correlation between the level of energy intake (p = 0.186), carbohydrate (p = 0.061), protein (0.576), fat (0.485) with the percentage of body fat among nutritional student of Public Health Faculty 2018. There was a correlation between body fat percentage (p = 0.034 ) with physical fitness, among 2018 Public Health Nutrition students. This study recommends that students pay attention to their eating habits and eating patterns in accordance with nutritional principles, so that the body can fulfill the nutrition that needed in order to improve their physical fitness.